Malignant Central Airway Obstruction due to Endotracheal Follicular Thyroid Cancer - Atif Saleem Siddiqui (Respirology Case Reports, 2025)
ABSTRACT A 69‐year‐old woman with airway obstruction due to endotracheal invasion by metastatic follicular thyroid carcinoma underwent rigid bronchoscopy with successful tumor excision. She received external beam radiation therapy with palliative intent. Bronchoscopic resection is a feasible and effective option for airway stabilisation in inoperable, refractory cases of endotracheal thyroid cancer.